Investigation of Surface Acoustic Wave Propagation Characteristics in New Multilayer Structure: SiO2/IDT/LiNbO3/Diamond/Si - Zhang, Hanqiang; Wang, Hongliang (Micromachines (Basel), 2021)
Surface acoustic wave (SAW) devices are widely used in many fields such as mobile communication, phased array radar, and wireless passive sensor systems. With the upgrade of mobile networks, the requirements for the performance of SAW devices have also increased, and high-frequency wideband SAW devices have become an important research topic in communication systems and other application fields. In this paper, a theoretical study for the realization of a layered SAW filter based on a new SiO2/IDT/128°YX-LiNbO3/diamond/silicon layered structure using the modeling software COMSOL Multiphysics is presented. The effects of lithium niobate (LiNbO3), an interdigital transducer (IDT), and SiO2 thin films on the evolution of the phase velocity, electromechanical coupling coefficient (k2), and temperature coefficient of frequency were studied by employing a finite element method simulation. Furthermore, a longitudinal coupling resonator filter was designed. To investigate the SAW characteristics of the filter, a transient analysis was conducted to calculate the electrical potential and particle displacement under the resonance condition and to analyze the frequency response. The study concluded that this new multilayer structure can be applied to design and manufacture a variety of high-frequency and wideband SAW filters with a temperature compensation function, for operation above the GHz range.